2002
DOI: 10.1136/thorax.57.2.142
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Burkholderia cepacia colonisation in an adult cystic fibrosis centre

Abstract: Background: Colonisation with Burkholderia cepacia is a poor prognostic indicator in subjects with cystic fibrosis (CF), but outcome prediction is impossible since patients are colonised by different strains with differing pathogenicity. The clinical course of a large cohort of CF patients colonised with UK epidemic (ET12) B cepacia was followed for 5 years and compared with that of the remaining patients in the clinic. Methods: Pulmonary function, nutritional state, and lung pathogen colonisation were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 36 publications
(30 reference statements)
2
62
0
2
Order By: Relevance
“…B. cepacia is a common pathogen in patients with CF (56), and previous studies have shown that intracellular persistence of the organism in CF macrophages is responsible for the infectious burden (57). In this study, the authors found that B. cepacia infection resulted in down-regulation of several autophagy genes in WT and DF508 macrophages, including Atg5, Atg12, and Atg8 (LC3B), with a more pronounced effect in the latter.…”
Section: Alveolar Macrophagessupporting
confidence: 52%
“…B. cepacia is a common pathogen in patients with CF (56), and previous studies have shown that intracellular persistence of the organism in CF macrophages is responsible for the infectious burden (57). In this study, the authors found that B. cepacia infection resulted in down-regulation of several autophagy genes in WT and DF508 macrophages, including Atg5, Atg12, and Atg8 (LC3B), with a more pronounced effect in the latter.…”
Section: Alveolar Macrophagessupporting
confidence: 52%
“…Clinical and biologic factors assessed included age and year of diagnosis, 18 sex, 19,20 CF transmembrane conductance regulator (CFTR) genotype, 19,21 infections with Pseudomonas aeruginosa or Burkholderia cepacia, 22,23 and CF-related diabetes (CFRD). 24 CFTR genotype severity was categorized into one of five functional classes proposed by Welsh et al 25 The mutations were further classified into three groups: "high" or "low" disease risk according to the scheme proposed by McKone et al 21 and "unclassified" disease risk for mutations with unknown functional class.…”
Section: Methodsmentioning
confidence: 99%
“…Infection with P aeruginosa or B cepacia was characterized as dichotomous (never/ever) and by age at first acquisition; earlier age at acquisition is associated with worse prognosis. 23,26,27 Diagnosis of CFRD was characterized as dichotomous (never/ever) and age at diagnosis. 24 Social factors assessed included public insurance status, median household income, 8,19 and access to subspecialty care.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work has demonstrated that the majority of infected CF patients harbor either B. cepacia genomovar III or Burkholderia multivorans (genomovar II) (1,25,38). Furthermore, limited data suggest that B. cepacia genomovar III (or perhaps certain specific strains within genomovar III) may be relatively more virulent than other species in this complex (3,12,19).The broad-spectrum antimicrobial resistance, absence of a vaccine, and virulence of certain strains have made prevention of B. cepacia complex infection an important goal in CF patient care (21, 22). However, much still remains unknown regarding the epidemiology of infection in CF.…”
mentioning
confidence: 99%